Corruption Crimes in Indonesia in Criminology Review - Mas Ahmad Yani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Based on the origin of the word (etymology), it can be stated that the meaning of corruption is something that expresses a condition that was once whole, good, and true, became unkind, not whole, and unrighteous as a result of such deeds; bribing, deceiving, faking, deforming, and such. The culprit is called a corruptor. What is considered a deterioration can be imposed on what concerns physical wholeness and moral integrity? Jeremy Bentham wrote that the term corruption used to be used in the physical sense, from there it was then used in the moral sense. Meanwhile, informal control can be carried out through preventive measures carried out independently by the wider community, both individual individuals and groups or institutional organizations outside the criminal justice system. Prevention can be done by, among others, developing a culture of shame and fear of doing wrong (moral sensibility), so that it can be created collectively self-policing attitudes in the midst of society, that committing acts of corruption is a despicable and evil act.